Upaya Peningkatan Kompetensi Guru Era 4.0 di Sekolah Indonesia Kuala Lumpur - Ratna Suhartini; Cholik, Mochamad; Tri Rijanto; Meini Sondang Sumbawati; Theodorus Wiyanto (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
Quality education is a crucial foundation for sustainable development, as emphasized in the Sustainable Development Goals (SDGs), particularly the fourth goal regarding inclusive and quality education. In the era of Industry 4.0, education must rapidly adapt to technological changes and enhance educators' competencies to equip the younger generation with future skills. Sekolah Indonesia Kuala Lumpur (SIKL) has adopted the K-13 Curriculum with the Living Curriculum concept to align learning with students' real needs and global challenges. Despite implementing various innovations, SIKL faces challenges in implementing the new Merdeka Curriculum, which offers flexibility but requires adjustments in teaching methods and evaluation. This knowledge gap threatens the quality of education and the development of 21st-century skills for students. To address this, a team of lecturers from Universitas Negeri Surabaya conducted a Community Service Program (CSP) aimed at enhancing teachers' competencies in effectively implementing the Merdeka Curriculum. The implementation method includes online training divided into three sessions: Focus Group Discussion (FGD), presentation of learning models, and evaluation techniques. The CSP activities resulted in a significant increase in teachers' understanding and skills, with average scores rising from 68 to 86, and improvements in utilizing technology and data-based evaluation. This activity successfully strengthened teachers' competencies, making them better prepared to meet global educational demands and advance teaching quality at SIKL.